Knowledge and Skills Enhancement Through Perioperative Nursing Simulation Lab Training - Whelan, Trish; Shi, Xinzhe; Yorke, Sue; Andony, Keith; McKenzie, Mary Lou (Operating Room Nurses Association of Canada Journal, 2016)
In Edmonton Zone, the attrition rate among new perioperative nursing staff is an issue of concern and many ORs are facing noticeable staffing challenges. In the Edmonton area there are approximately 79 surgical suites. A series of simulation labs were established in 2015 to provide perioperative nurses in order to increase their comfort on the job and to help build confidence levels. The expectations for this simulation are an overall improvement in perioperative nurses’ competency, a reduction in OR orientation and training time, and a decrease in the attrition rates among OR nurses.